Mammal - Parker, Steve, 1952- (New York : Knopf : Distributed by Random House, 1989)
Photographs and text examine the world of mammals, depicting their development, feeding habits, courtship rituals, protective behavior, and physical adaptation to their various ways of life.
"A Dorling Kindersley book"--T.p. verso.
Includes index.
Wilson's Children, November 1996.
Wilson's Junior High School, September 1995.
Elem. School Library Collection, March 1998.
Booklist starred, January 2011.
Keywords: Mammals -- Juvenile literature; Mammals; Mammals; Mammals